Negotiating Climate Change in Crisis - Böhm, Steffen; Sullivan, SIan (Open textbook library., 2021)
Climate change negotiations have failed the world. Despite more than thirty years of high-level, global talks on climate change, we are still seeing carbon emissions rise dramatically. This edited volume, comprising leading and emerging scholars and climate activists from around the world, takes a critical look at what has gone wrong and what is to be done to create more decisive action. Composed of twenty-eight essays—a combination of new and republished texts—the anthology is organised around seven main themes: paradigms; what counts?; extraction; dispatches from a climate change frontline country; governance; finance; and action(s). Through this multifaceted approach, the contributors ask pressing questions about how we conceptualise and respond to the climate crisis, providing both ‘big picture’ perspectives and more focussed case studies. This unique and extensive collection will be of great value to environmental and social scientists alike, as well as to the general reader interested in understanding current views on the climate crisis.